2021
DOI: 10.1111/jocn.15713
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock: Clinical indicators and implications to critical patient care

Abstract: Aims and Objective To identify clinical indicators of septic shock in critical care patients. Background The identification of clinical indicators of septic shock is relevant to avoid clinical deterioration of patients with sepsis. However, the recognition of these factors, especially by the nursing team, is still deficient and reinforces the need for studies that investigate the subject in different realities such as that of Brazil. Design The study had a cross‐sectional design based on STROBE guidelines (see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
12

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 24 publications
0
3
0
12
Order By: Relevance
“…Pinto et al (9) observaram que existe maior risco de desenvolvimento de choque séptico nos doentes provenientes do SU do que daqueles transferidos de outras unidades hospitalares, sendo que os sinais e sintomas mais regularmente apresentados nas primeiras 6 horas foram: taquicardia > 90 bpm; taquipneia > 20 cpm; leucopenia < 4000/mm 3 ; leucocitose > 12 000/mm 3 ; SpO 2 < 90%; hipertermia > 38,3ºC; e hipotermia < 36ºC. Como indicadores de choque séptico, foram também identificados: hipotensão; suporte por VMI; hipotermia; lactatos > 2 mmol/L; radioterapia associada a quimioterapia; score SOFA > 3; e admissão pelo SU.…”
Section: Intervenções Especializadas à Pessoa Em Situação Crítica Em ...unclassified
See 1 more Smart Citation
“…Pinto et al (9) observaram que existe maior risco de desenvolvimento de choque séptico nos doentes provenientes do SU do que daqueles transferidos de outras unidades hospitalares, sendo que os sinais e sintomas mais regularmente apresentados nas primeiras 6 horas foram: taquicardia > 90 bpm; taquipneia > 20 cpm; leucopenia < 4000/mm 3 ; leucocitose > 12 000/mm 3 ; SpO 2 < 90%; hipertermia > 38,3ºC; e hipotermia < 36ºC. Como indicadores de choque séptico, foram também identificados: hipotensão; suporte por VMI; hipotermia; lactatos > 2 mmol/L; radioterapia associada a quimioterapia; score SOFA > 3; e admissão pelo SU.…”
Section: Intervenções Especializadas à Pessoa Em Situação Crítica Em ...unclassified
“…Associado ao choque séptico, o órgão mais afetado é o cardiovascular, motivo pela qual a hipotensão se apresentar como um dos sintomas mais usuais (9) . Este é também verificado por Jeganathan et al (15) que, no seu estudo, referem que 52% dos seus doentes em choque séptico, teve presente disfunção cardiovascular.…”
Section: Intervenções Especializadas à Pessoa Em Situação Crítica Em ...unclassified
“…Apart from diagnosis, sepsis management guidelines majorly concentrated on three windows i.e. , hemodynamic steadiness, contagion control and intonation of the septic responses [ 8 ]. Some of the other intrusions include fewer specific parameters of organ support like ventilation on a mechanical basis, oxygen therapy, renal replacement therapy, corticosteroids, and hemodynamic support [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the ‘Surviving Sepsis Campaign’ (SSC) guidelines, the importance of hospitals and hospital systems for sepsis screening for acute and high‐risk patients was emphasised (Levy et al, 2018; Rhodes et al, 2017). Intensive care nurses serving high‐risk critical patients for sepsis should also have a more advanced level of sepsis awareness and screening and management skills compared with nurses working in other units of hospitals (Bleakley & Cole, 2020; Pinto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted in Turkey indicated that mortality in sepsis was 31.2% in ICU, it was 75.9% in septic shock (Baykara et al, 2018), and the cost of sepsis treatment constituted 39.2% of the total treatment costs (Azap et al, 2019). It was found that 49% of the patients followed up in ICUs in Brazil over a one‐year period were admitted to the unit due to septic shock and that 44.7% of these patients were discharged and 55.2% died (Pinto et al, 2021). While sepsis increases mortality rates and costs, physical and cognitive functions in patients after sepsis are significantly reduced, and it causes repeated hospitalisations (Gauger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%